The The Effect of Rainfall Intensity on Slope Stability: An Analytical Study using Numerical Modeling - Jamel, Asmaa Abdul Jabbar (Engineering, Technology & Applied Science Research, 2025)
Slope instability causes landslides, which have a detrimental effect on infrastructure and the environment while contributing to significant damage both in terms of people and property. The present article offers a thorough examination of slope stability by SEEP/W and SLOPE/W software programs. Using numerical simulations based on three different models, the work plan analyzed changes in moisture content, Pore Water Pressure (PWP), and factor of safety (F.S.) to assess the impact of a set of hydrological and engineering factors, such as rainfall intensity (I), soil permeability (K), and slope angles (S). Based on the results, PWP rises to 185.84 kPa and the F.S. drops to 1.233 as rainfall intensity exceeds 80 mm/h. Additionally, longer rainfall intervals (3 days) result in a 20% reduction in F.S. as compared to short rainfall periods. The study also found that steep slopes (30° or more) greatly enhance the chance of falling apart, particularly in highly permeable soils, while the rapid water seepage along gradients caused by highly permeable soils increases the danger of collapse. The findings suggest that, in addition to enhancing soil qualities in high-permeability areas and utilizing efficient drainage systems to lower pore pressure, engineering projects should consider the impact of heavy rainfall and extended precipitation. Furthermore, a novel mathematical equation was developed to calculate the F.S. of slopes, incorporating key parameters, such as rainfall intensity, slope angle, and soil type. This equation underwent rigorous statistical analysis, achieving the highest accuracy rate, and can serve as a robust tool for slope stability assessment in diverse environmental and engineering scenarios.